p27(Kip1) nuclear localization and cyclin-dependent kinase inhibitory activity are regulated by glycogen synthase kinase-3 in human colon cancer cells - Wang, Qingding (2008)
The cellular mechanisms regulating intestinal differentiation are poorly understood. Sodium butyrate (NaBT), a short chain fatty acid, increases p27(Kip1) expression and induces cell cycle arrest associated with intestinal cell differentiation. Here, we show that treatment of intestinal-derived cells with NaBT induced G0/G1 arrest and intestinal alkaline phosphatase, a marker of differentiation, activity and mRNA expression; this induction was attenuated by inhibition of glycogen synthase kinase-3 (GSK-3). Moreover, treatment with NaBT increased the nuclear, but not the cytosolic, expression and activity of GSK-3β. NaBT decreased CDK2 activity and induced p27(Kip1) expression; inhibition of GSK-3 rescued NaBT-inhibited CDK2 activity and blocked NaBT-induced p27(Kip1) expression in the nucleus but not in the cytoplasm. In addition, we demonstrate that NaBT decreased the expression of Skp2 protein, and this decrease was attenuated by GSK-3 inhibition. Furthermore, NaBT increased p27(Kip1) binding to CDK2 which was completely abolished by GSK-3 inhibition. Overexpression of an active form of GSK-3β reduced Skp2 expression, increased p27(Kip1) in the nucleus and increased p27(Kip1) binding to CDK2. Our results suggest that GSK-3 not only regulates nuclear p27(Kip1) expression through the down-regulation of nuclear Skp2 expression but also functions to regulate p27(Kip1) assembly with CDK2, thereby playing a critical role in the G0/G1 arrest associated with intestinal cell differentiation.